Impact of fractional frequency reuse in reducing inter-cell interference LTE.. (Revista de Investigaciones Universidad del Quindío, 2014)
The Inter-Cell Interference (ICI) is a problem that impacts the performance of Long Term Evolution (LTE) networks, however there are techniques like Inter-Cell Interference Coordination (ICIC) as Fractional Frequency Reuse (FFR) that mitigate the interference and improve the performance of User Equipment (UE), especially those terminals on the edge cell. This article focuses on the Fractional Frequency Reuse (FFR) performance in LTE, according two configuration parameters: Threshold Signal to Interference plus Noise Ratio (SINR) and partition Bandwidth (BW). Capacity and interference were evaluated by scatter plots, Empirical Cumulative Density Function (ECDF) curves and statistical calculations.
Keywords: ICI; FFR; LTE; Performance; SINR; Spectral Efficiency; Throughput